Ibuprofen encapsulation inside non-conventional O/W Pickering emulsions stabilized with partially hydrophobized silica - Ramos, Diego; Sapin-Minet, Anne; Marchal, Philippe; Parent, Marianne; Sadtler, Véronique; Roques-Carmes, Thibault (Frontiers in Coatings, Dyes and Interface Engineering, 2024)
The encapsulation of active ingredients is an important process in various industrial sectors including pharmaceutics, foods and cosmetics. For the first time, the capacity of non-conventional anti-Bancroft oil-in-water Pickering emulsions stabilized by partially hydrophobized silica to encapsulate an apolar active is addressed. A dispersed phase volume of paraffin oil of 50% coupled to 0.5 wt.% of silica has been employed to avoid excess of silica in the continuous phase and encapsulate higher amount of ibuprofen (the model drug). Three ibuprofen contents ranging from 100 mg (1.6 mg/mL of paraffin) to 420 mg (6 mg/mL of paraffin) have been tested. The encapsulation efficiency as well as the emulsions properties are investigated by the means of light diffusion, microscopy, rheology, and HPLC coupled to mass balance. The Pickering emulsion is very efficient for the encapsulation of ibuprofen with encapsulation rates of 99% obtained inside droplets of 30 µm for all the 3 ibuprofen concentrations. This encapsulation ability is perfectly maintained, whether during ageing (during 90 days), or when the emulsion is diluted by a factor 100 inside physiological media at basic and acidic pH.